(untitled) (Modern education and development, 2024)
the article analyzes the importance of the field of cyber law and its role in modern society, key concepts of cyber law, the interconnection between cyberspace and Human Rights, and security issues in the digital age. The article covered current issues such as cybercrime, protection of personal information, intellectual property rights and freedom of expression on the internet.